2021
DOI: 10.3390/nu13061892
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Maternal Energy Intake during Lactation Decreased Maternal Body Weight and Concentrations of Leptin, Insulin and Adiponectin in Human Milk without Affecting Milk Production, Milk Macronutrient Composition or Infant Growth

Abstract: Maternal diet has the potential to affect human milk (HM) composition, but very few studies have directly assessed the effect of maternal diets on HM composition. The primary aim of this study was to assess the effect of improving dietary quality in lactating women over 2 weeks on the concentrations of macronutrients and metabolic hormones in HM. The secondary aims were to assess the impact of the dietary intervention on 24 h milk production, maternal body composition and infant growth. Fifteen women completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 52 publications
1
22
0
1
Order By: Relevance
“…31 To date, only two interventional studies have assessed the effect of maternal diet on HM macronutrient composition. 26,32 An 8 days high-fat diet intervention resulted in increased HM total lipid concentrations. The same women then followed a low-fat diet for the same period, with no change in HM lipid content.…”
Section: Maternal D Ie Tmentioning
confidence: 99%
See 3 more Smart Citations
“…31 To date, only two interventional studies have assessed the effect of maternal diet on HM macronutrient composition. 26,32 An 8 days high-fat diet intervention resulted in increased HM total lipid concentrations. The same women then followed a low-fat diet for the same period, with no change in HM lipid content.…”
Section: Maternal D Ie Tmentioning
confidence: 99%
“…HM micronutrients, including vitamins (A, E, C, B1, B12), calcium and copper, have been shown to associate positively with maternal dietary intake levels 31 . To date, only two interventional studies have assessed the effect of maternal diet on HM macronutrient composition 26,32 . An 8 days high‐fat diet intervention resulted in increased HM total lipid concentrations.…”
Section: Maternal Dietmentioning
confidence: 99%
See 2 more Smart Citations
“…As with leptin, there are studies reporting both presence and absence of such associations [ 170 ]. To add to the complexity further, we have shown that HM total protein concentration does not change day-to-day [ 180 ], week-to-week [ 181 ] or during a short maternal dietary intervention [ 182 ].…”
Section: Influences Of Maternal Body Composition On Milk Compositionmentioning
confidence: 99%